Pembentukan Nilai Sosial Generasi Z Melalui Praktik Perjamuan Kudus Anak di Gereja Kristen Jawa Dagen Palur Karanganyar - Justin Niaga Siman Juntak; Yance Z. Rumahuru; Agusthina Christina Kakiay (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2026)
This study aims to examine the formation of social and spiritual values among Generation Z children through the practice of Children’s Holy Communion at Gereja Kristen Jawa (GKJ) Dagen Palur Karanganyar as a contextual model of faith education. This research employs a qualitative approach. The findings reveal that Children’s Holy Communion plays a significant role in shaping both social and spiritual values. Socially, children demonstrate increased empathy, patience, care for others, discipline, responsibility, and a sense of belonging within family and church communities. Spiritually, they experience a deeper understanding of faith, greater appreciation of the symbolic meaning of bread and wine, and a growing awareness of their identity as members of the body of Christ. The formation of these values occurs through a continuous process that includes pre-communion instruction, active participation in worship, and post-communion involvement in church life. These findings indicate that Children’s Holy Communion functions not merely as a liturgical ritual, but as a holistic means of faith formation that integrates cognitive, affective, social, and spiritual dimensions of Generation Z children.